WLAN's access points java based automatic location tool (2007)
In this paper, we will show the development process and the results obtained with a Java based toll for automatic location of WLAN Access Points. We will describe the algorithm developed and the results obtained until the time we wrote the paper. Also we will discuss future work and possible evolution for the tool.